PathoGraphics Narrative, Aesthetics, Contention, Community - Squier, Susan M; Krüger-Fürhoff, Irmela Marei (Penn State University Press, 2020)
Culturally powerful ideas of normalcy and deviation, individual responsibility, and what is medically feasible shape the ways in which we live with illness and disability. The essays in this volume show how illness narratives expressed in a variety of forms-biographical essays, fictional texts, cartoons, graphic novels, and comics-reflect on and grapple with the fact that these human experiences are socially embedded and culturally shaped. Works of fiction addressing the impact of an illness or disability; autobiographies and memoirs exploring an experience of medical treatment; and comics that portray illness or disability from the perspective of patient, family member, or caregiver: all of these narratives forge a specific aesthetic in order to communicate their understanding of the human condition. This collection demonstrates what can emerge when scholars and artists interested in fiction, life-writing, and comics collaborate to explore how various media portray illness, medical treatment, and disability. Rather than stopping at the limits of genre or medium, the essays talk across fields, exploring together how works in these different forms craft narratives and aesthetics to negotiate contention and build community around those experiences and to discover how the knowledge and experiences of illness and disability circulate within the realms of medicine, art, the personal, and the cultural. Ultimately, they demonstrate a common purpose: to examine the ways comics and literary texts build an audience and galvanize not just empathy but also action. In addition to the editors, the contributors to this volume include Einat Avrahami, Maureen Burdock, Elizabeth J. Donaldson, Ariela Freedman, Rieke Jordan, stef lenk, Leah Misemer, Tahneer Oksman, Nina Schmidt, and Helen Spandler.